Effects of Noise Type and Noise Sensitivity on Working Memory and Noise Annoyance. - Song, Chen; Li, Hongqidi; Ma, Huirui; Han, Tao; Wu, Jianping (Noise & Health)
Objective: This study explored the interaction between environment and behavior and analyzed the effect of physical environment stimuli and individual differences on environmental perception.Methods: We investigated the effects of two kinds of noise sensitivities (high sensitivity and low sensitivity) and three kinds of noise types (quiet, road traffic noise, and speech noise) on working memory and noise annoyance of college students through questionnaires and experiments.Results: (i) noise sensitivity was positively correlated with neuroticism and negatively correlated with conscientiousness. (ii) The interaction between noise sensitivity and noise type significantly affected the accuracy of working memory. (iii) Both noise sensitivity and the main effect of noise type significantly affected the response time of working memory. (iv) The interaction between noise sensitivity and noise type significantly affects noise annoyance.Conclusion: There were significant differences in working memory performance and subjective noise annoyance among individuals with different levels of noise sensitivity.